The Truly Vulnerable: Integrating Wealth into the Measurement of Poverty and Social Policy Effectiveness - Sarah Kuypers; Ive Marx (Institute of Labor Economics (IZA), 2017)
There is a burgeoning literature on the significance and distribution of wealth in the rich world. It mainly focuses on the top. Wealth remains remarkably absent from the analysis of poverty and the redistributive effectiveness of welfare systems. This paper shows that real and financial assets can matter greatly when making assessments of who is poor and financially vulnerable. We introduce the concept of triple precariousness, afflicting households that not only have low income but also very low or non-existent assets to draw on for consumption needs, especially liquid assets. We analyse whether these households – whom we might call the truly vulnerable – have different characteristics from those that we identify as poor or needy on the basis of pure income based metrics. In an analysis for Belgium drawing on HFCS data, we show that households with a reference person that is young, unemployed, low educated, migrant, parent of dependent children, and above all a tenant are especially vulnerable in terms of their financial situation. By contrast, our assessment of the extent and depth of financial need among the elderly – a segment of society that is at a relatively high risk of income poverty – also changes. A substantial share of income poor elderly households own significant assets. We draw out some tentative consequences of these findings for anti-poverty and redistributive policies.
Keywords: D31; G11; 330; low income; low wealth; asset portfolio; social policy